Dissociating executive mechanisms of task control following frontal lobe damage and Parkinson's disease. - Rogers, R; Sahakian, B; Hodges, JR; Polkey, C; Kennard, C; Robbins, T (1998)
Twelve patients with focal damage of the frontal cortex and 12 patients with mild, medicated, early stage Parkinson's disease switched between letter- and digit=naming tasks on every second trial of a task-switching paradigm. Compared with age- and IQ-matched control performance, patients with left-sided, but not right-sided, frontal damage exhibited markedly increased time costs associated with these predictable switches only when there was a general incidence of interference or 'crosstalk' between the tasks, and particularly so when the available task cues were relatively weak and arbitrary. The same patients also showed evidence of an increased sensitivity to the facilitatory and inhibitory effects of previous processing, when required to switch between tasks. Both groups of patients (with left- or right-sided frontal damage) exhibited slow, disorganized performance early in practice. In contrast to these frontal effects, the Parkinson's disease patients showed little indication of larger time costs of task switches but they did show progressive increases in the error costs, while age- and IQ-matched control subjects showed reductions. We propose that while both left and right frontal cortical areas are involved in the organization of cognitive and motor processes in situations involving novel task demands, only the left frontal cortex is involved in the dynamic reconfiguring between already-established task-sets, and specifically, that it is the site of an executive mechanism responsible for the modulation of exogenous task-set activity. Finally, dopaminergic transmission, along the nigrostriatal pathway, may be implicated in sustaining various cognitive and motor processes over prolonged periods, including the operation of those executive control mechanisms that accomplish reconfiguring between task-sets.